Accumulation of soil microbial necromass carbon and its contribution to soil organic carbon after vegetation restoration in the Tibetan Plateau - Xiangjun Pei; Junjie Lei; Xiaodong Wang; Yang Xiao; Zhihan Yang; Runying Zhao; Cangli Zeng; Zhenyu Luo; Jingji Li; Ningfei Lei; Qingwen Yang; Shuming Peng; et al. (Global Ecology and Conservation)
Vegetation restoration has been proved as an effective strategy to increase soil organic carbon (SOC) sequestration in degraded ecosystems. However, due to different vegetation restoration practices and climate zones, changes of SOC content, dynamics, sources and their controlling mechanisms after vegetation restoration remain inadequately addressed. Taking the advantage of four-year vegetation restoration, we explored the effects of vegetation restoration on SOC content through its fractions, soil aggregates, soil enzymes and microbial necromass contribution to SOC in a desertification region in the Tibetan Plateau (TP). Results showed that vegetation restoration increased SOC contents by 68 % for 0 – 10 cm, 29 % for 10 – 30 cm and 11 % for 30 – 50 cm compared to site without vegetation restoration. Vegetation restoration increased soil macroaggregates (> 0.25 mm) and decreased soil microaggregates (0.53 – 0.25 mm), but increased their associated SOC contents. Meanwhile, vegetation restoration enhanced microbial necromass and its contribution to SOC. Structural equation model revealed that increasing microbial necromass carbon, changing soil aggregates and their associated SOC were the main mechanisms of increasing SOC content after vegetation restoration. Our result further indicated a large potential of SOC sequestration through vegetation restoration in the TP. These findings have important implications for natural based solution for carbon neutrality for China.